AfCFTA implementation challenges: Towards an African continental textiles and apparel value chain - Poorva Karkare; Bruce Byiers; Amanda Bisong; Faizel Ismail; Prachi Agarwal; Christopher McKaige (ODI Global, 2025)
The African Continental Free Trade Area (AfCFTA) promises a new era of economic integration and industrial growth across the continent. But how can Africa truly harness this potential, especially in the vital textiles and apparel sector? This report explores the key challenges and opportunities in establishing a thriving, continent-wide textile and apparel regional value chain (RVC). The research offers essential insights into how harmonised trade rules, strategic investments, and regional collaboration can transform Africa's diverse textile landscape into a powerhouse of economic transformation. The textiles and apparel industry has long been a proven pathway to manufacturing development. Yet, significant obstacles remain, such as stalled negotiations around Rules of Origin (RoO) and a prevailing focus on low-value-added activities like apparel assembly. This analysis highlights the complex political and economic dynamics shaping the sector and explores how the AfCFTA framework can attract investment, shift sourcing patterns, and expand intra-African sales. It also examines the crucial interplay between participating in global value chains for knowledge transfer and fostering homegrown brands for the African market.
Keywords: 330; Economic growth; Africa; Trade & investment